Income and Financial Trends for Kansas Farms - Langemeier, Larry N. (My University, 1995)
This publication uses data provided by farms enrolled in the Kansas Farm Management Association program to make income and financial ratio trends.
MF801_1995_10
Keywords: MF801; Economics; MF